A Study on Fixed-Point Techniques under the α-ϝ-Convex Contraction with an Application - Gunasekaran Nallaselli; Arul Joseph Gnanaprakasam; Gunaseelan Mani; Ozgur Ege; Dania Santina; Nabil Mlaiki (Axioms, 2023)
In this paper, we consider several classes of mappings related to the class of <semantics>α</semantics>-<semantics>ϝ</semantics>-contraction mappings by introducing a convexity condition and establish some fixed-point theorems for such mappings in complete metric spaces. The present result extends and generalizes the well-known results of <semantics>α</semantics>-admissible and convex contraction mapping and many others in the existing literature. An illustrative example is also provided to exhibit the utility of our main results. Finally, we derive the existence and uniqueness of a solution to an integral equation to support our main result and give a numerical example to validate the application of our obtained results.